Evaluation of the Influence of E-Service Quality and E-Trust on Customer Loyalty in Digital Banking Services: Evidence from Indonesian State-Owned Banks (BUMN) - Mardhatilah, Asri Cahya; Awalia , Dita Novia (Smart International Management Journal, 2025)
The rapid advancement of digital transformation has intensified competition among Indonesian State-Owned Banks (BUMN), making digital banking services a strategic focus for sustaining customer loyalty. This study investigates the simultaneous and partial effects of Electronic Service Quality (E-Service Quality) and Electronic Trust (E-Trust) on Customer Loyalty in BUMN digital banking. A quantitative approach is employed using secondary panel data from 2020–2024 obtained from Bank Indonesia (BI), the Financial Services Authority (OJK), and the Indonesia Stock Exchange (BEI). Customer Loyalty is proxied by third-party fund (DPK) growth and digital transaction volumes, while E-Service Quality is represented by customer complaint data reported to OJK. Panel data regression analysis reveals that both E-Service Quality and E-Trust have a positive and statistically significant effect on Customer Loyalty. Importantly, E-Trust demonstrates a stronger influence, emphasizing the critical role of customer confidence in digital banking retention. These findings highlight the need for BUMN banks to improve system reliability and user experience while prioritizing transparency, data security, and regulatory compliance. This study contributes to the digital banking literature by integrating regulatory-based indicators with customer loyalty outcomes.